1997
DOI: 10.1002/jobm.3620370612
|View full text |Cite
|
Sign up to set email alerts
|

Microbial populations associated with commercial bread production

Abstract: The microbial ecology of a commercial bread production line was assessed by plate counts and characterization of microbial populations of raw materials, dough, equipment surfaces, air inside the bakery and baked bread. Aerobic plate counts for raw materials were higher than mould counts. Dough samples had high aerobic plate counts, but low mould counts. Mould counts on pre-baking equipment surfaces were lower than those on post-baking equipment surfaces, while aerobic plate counts on equipment surfaces varied.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 5 publications
(10 reference statements)
1
12
0
Order By: Relevance
“…Dishes of different diameters, different exposure times, different nutrient media and different incubation temperatures and times, make it difficult to compare data obtained by different operators. [62][63][64][65][66][67] Moreover, a rating of the results obtained by settle plates has never been established.…”
Section: Attempts To Standardize Passive Air Samplingmentioning
confidence: 99%
“…Dishes of different diameters, different exposure times, different nutrient media and different incubation temperatures and times, make it difficult to compare data obtained by different operators. [62][63][64][65][66][67] Moreover, a rating of the results obtained by settle plates has never been established.…”
Section: Attempts To Standardize Passive Air Samplingmentioning
confidence: 99%
“…As shown in Table 2, the numbers of TAMB, Bacillus spore and yeast and mold counts were found higher in the dough with added antimicrobial (calcium propionate) than in the dough without Ca-propionate. [19] In a similar research, TAMB and yeast-mold counts were found more often in the dough samples than bread samples.…”
Section: Results Of Microbiological Physical and Chemical Analyses mentioning
confidence: 74%
“…Viljoen et al [19] also reported that TAMB counts were greater than yeast and mold counts for all partbaking and storage times. Viljoen et al [19] also reported that TAMB counts were greater than yeast and mold counts for all partbaking and storage times.…”
Section: Part-baked White Pan Breads Without Storagementioning
confidence: 90%
“…can survive the baking process in the centre of the crumb. After the cooling of the bread, under favorable conditions, spores can germinate and grow as vegetative cells producing a deterioration process of bread texture characterized by ropiness, sticky crumb, and a rotting pineapple odor (Doyle and others ; Viljoen and von Holy, ). Moreover, several studies reported the identification of different spore‐forming bacteria associated with the ropy spoilage of bread (Valerio and others ).…”
Section: Resultsmentioning
confidence: 99%